Keterbukaan Status HIV dan Penggunaan Kondom pada Pasangan HIV-SERODISCORDANT - Aries Sulaiman; Sri Yona; Riri Maria (FORIKES, 2021)
The number of sufferers incouples serodiscordant is greater than incouples seroconcordant (both HIV positive partners). Disclosure of HIV status or disclosure plays an important role in preventing transmission in seronegative partners. The purpose of this paper is to provide an overview of the relationship of disclosure or openness of HIV status (Human Immunodeficiency Virus) to one's partner and the use of condoms to the risk of transmission in HIV couples serodiscordant. This literature study used analysis of articles from several well-known databases namely Science Direct, ClinicalKey and EBSCO from 2008 to 2020. The keywords used when searching were disclosure and HIV serodiscordant and condom use. In this literature study, 16 articles were found that fulfilled the inclusion and exclusion criteria from 317 articles found. Some of the factors that make it difficult for an individual to be open about their status with their partners are anxiety about being abandoned, fear of being blamed, and divorce. Strengthening pre and post-test counseling properly can help resolve conflicts incouples serodiscordant. Until now, efforts to suppress transmission in negative couples have been using condoms. Keywords: HIV disclosure; HIV serodiscordant; condom use ABSTRAK Jumlah penderita pada pasangan serodiscordant lebih besar dibandingkan dengan pasangan seroconcordan (kedua pasangan positif HIV). Keterbukaan status atau disclosure berperan penting dalam mencegah transmisi pada pasangan yang seronegatif. Tujuan penulisan literatur review ini adalah untuk memberikan gambaran bagaimana hubungan keterbukaan status HIV (Human Immunodeficiency Virus) seseorang terhadap pasangannya dan penggunaan kondom terhadap resiko penularan pada pasangan HIV serodiscordant. Studi literatur ini menggunakan analisis artikel-artikel dari beberapa database yang ternama yaitu Science Direct, ClinicalKey dan EBSCO dari tahun 2008 sampai 2020. Kata kunci yang digunakan yaitu disclosure and hiv serodiscordant and condom use. Pada studi literatur ini didapatkan 16 artikel yang memenuhi syarat kriteria inklusi dan ekslusi dari 317 artikel yang ditemukan. Beberapa faktor yang menyebabkan sulitnya individu terbuka mengenai statusnya terhadap pasangannya adalah kecemasan akan ditinggalkan, takut disalahkan, dan perceraian. Penguatan konseling pre dan post-test secara baik dapat membantu menyelesaikan konflik pada pasangan serodiscordant. Sampai saat ini upaya dalam menekan penularan pada pasangan yang negatif adalah penggunaan kondom. Kata kunci: keterbukaan; HIV serodiscordant; penggunaan kondom